ROAD INFRASTRUCTURE ARRANGEMENT IN THE FISHERMAN VILLAGE RESIDENTIAL ENVIRONMENT ACROSS BELAWAN - Azhar Paras Muda Hasibuan; Feby Milanie; Ruth Riah Ate Tarigan (Bulletin of Engineering Science, Technology and Industry, 2025)
Environmental infrastructure planning that is effective and appropriate plays an important role in increasing the productivity of fishing communities and supporting sustainable regional development. Kampung Nelayan Seberang Belawan, where the majority of residents depend on the fisheries sector, requires better environmental infrastructure planning to support fishing activities and improve community welfare. This study aims to analyze the existing infrastructure conditions, identify environmental infrastructure needs, and formulate appropriate strategies for environmental infrastructure planning to enhance fishermen's urgent productivity and support regional development. The research uses a qualitative method with a case study approach, interviews, and direct observation. The results show that the current environmental infrastructure is inadequate. Coastal protection infrastructure, such as wave barriers and mangrove planting, is crucial for maintaining environmental resilience and preventing damage caused by abrasion and natural disasters. Proper management of waste and domestic wastewater will also improve environmental quality and public health. The provision of better educational and health facilities will improve the quality of life for fishing communities and create opportunities for a more creative and technologically literate younger generation. This has a positive impact on the environmental infrastructure planning of Kampung Nelayan Seberang in regional development. The planning of environmental infrastructure in Kampung Nelayan Seberang constitutes a strategic key in developing competitive coastal areas. The success of this arrangement greatly depends on multi-party collaboration, sustainable planning, and policy support for marginal areas. By maximizing strengths and opportunities and mitigating weaknesses and threats, this area can grow into an inclusive and productive community.